The effectiveness of policy and strategy of Malaysian Maritime transportation / Sarizan Nordin. - Nordin, Sarizan (1991)
Much has been said about making Malaysia a "Maritime Nation", whatever it is perceived to be. For the last ten years or so, it has been popular buzz - word in the Malaysian shipping industry and among local authorities on transport and infrastructure. Despite the frequent reference, various quarters within the industry .probably do not have common understanding of the objectives, neither are aware of any official document which clearly defines the goal and its implementation. But, what matters is that the inferred objectives seems to be logical targets as seaborne transport has been and will continue to be the single -most important channel of international trade in the foreseeable future. Malaysia's heavy trade orientation and rapid industrial growth must be backed by an efficient seaborne transport infrastructure, owned and manage by Malaysian. The shipping industry is multi - faceted, with many activity groups such as ship-owners, ports, shippers and Government. Even parties within each of these groups are often structurally diverse and tend to have their own ideas on maritime development. This study will view the growth of Marine Industry in general and how far are we ready to take the challenge of being a Maritime Nation.